Review on recent advancements in the role of electrolytes and electrode materials on supercapacitor performances - Ashutosh Patel; Suresh Kumar Patel; R. S. Singh; R. P. Patel (Discover Nano)
Abstract Supercapacitors currently hold a prominent position in energy storage systems due to their exceptionally high power density, although they fall behind batteries and fuel cells in terms of energy density. This paper examines contemporary approaches aimed at enhancing the energy density of supercapacitors by adopting hybrid configurations, alongside considerations of their power density, rate capability, and cycle stability. Given that electrodes play a pivotal role in supercapacitor cells, this review focuses on the design of hybrid electrode structures with elevated specific capacitance, shedding light on the underlying mechanisms. Factors such as available surface area, porosity, and conductivity of the constituent materials significantly influence electrode performance, prompting the adoption of strategies such as nanostructuring. Additionally, the paper delves into the impact of novel bio-based hybrid electrolytes, drawing upon literature data to outline the fabrication of various hybrid electrode materials incorporating conducting polymers like polyaniline and polypyrrole, as well as metal oxides, carbon compounds, and hybrid electrolytes such as ionic liquids, gel polymers, aqueous, and solid polymer electrolytes. The discussion explores the contributions of different components and methodologies to overall capacitance, with a primary emphasis on the mechanisms of energy storage through non-faradic electrical double-layer capacitance and faradaic pseudo-capacitance. Furthermore, the paper addresses the electrochemical performance of hybrid components, examining their concentrations and functioning via diverse charge storage techniques.